PENGARUH HERBISIDA BERBAHAN AKTIF PARAQUAT TERHADAP PERSENTASE KEMATIAN GULMA DAN JUMLAH MIKROORGANISME TANAH - Sakiah Sakiah; Guntoro Guntoro; Adri Moses Manullang (Institut Teknologi Sawit Indonesia, 2020)
Paraquat is an active herbicide used to control weeds chemically. This research aim is to determine the effect of herbicide applications with active paraquat matters on the percentage of weed mortality and the number of soil microorganisms. This research used a non-factorial randomized block design with five levels of treatment, that is P0: control; P1: 5 ml of paraquat in 1 litre of water, frequency of application is once a week; P2: 10 ml of paraquat in 1 litre of water, frequency of application is once a week; P3: 10 ml of paraquat in 1 litre of water, frequency of application is once in two weeks; and P4: 5 ml of paraquat in 1 litre of water, frequency of application is once in two weeks. The results of the observations were compiled in a Variety Checklist and continued with the Duncan Multiple Range Test. The results showed that the dominant weeds in the research plot were Ageratum conyzoides, Mimosa pudica, and Paspalum commersonii.The application of 5 ml/l paraquat herbicide, the frequency of application once a week was effective in reducing weed mortality. However, the use of paraquat did not significantly affect the number of soil microorganisms